Eat to beat your diet : burn fat, heal your metabolism, and live longer - Li, William W. (Balance, 2023)
"Dr. Li introduces the surprising new science of weight loss, revealing healthy body fat can help you lose weight; your metabolism at 60 can be the same as when you were 20; yo-yo dieting can be good for your health; 8-hour fasting windows can be as effective as 12-hour fasting windows; and losing just a little bit of weight can have big impacts on your health. Eat to Beat Your Diet shows readers how adding the right foods to your diet can heal your metabolism, reduce unhealthy body fat, and result in the kind of weight loss that can increase your lifespan and help you thrive"--